Use of Khat and Posttraumatic Stress Disorder as Risk Factors for Psychotic Symptoms : A Study of Somali Combatants - Odenwald, M.; Hinkel, H.; Schauer, E.; Schauer, M.; Elbert, T.; Neuner, F.; Rockstroh, B. (2012)
The chewing of the khat leaves, which contain the amphetamine-like cathinone, is a traditional habit in Somalia. Our objective was to explore the effects of khat use and Posttraumatic Stress Disorder (PTSD) on paranoid symptoms and to test a potential causal chain. We report on a cross-sectional study in Somalia that was conducted in 2003. Trained local staff interviewed 8723 personnel of armed groups in seven regional convenience samples. Of them, 8124 were included in the analysis. We assessed current khat use, PTSD symptoms, functional drug use and paranoid ideation using items from the Composite International Diagnostic Interview (CIDI) and the Somali version of the Posttraumatic Stress Diagnostic Scale (PDS). Applying the causal steps approach, in a series of logistic regression models, we used PTSD as independent and paranoia as outcome variable; the quantity of khat use was defined as mediator variable and functional drug use as moderator. The results showed that respondents with PTSD used khat more frequently. Khat chewers with PTSD reported a higher intake compared to khat chewers without PTSD. Among excessive khat chewers with PTSD, paranoia was most frequent. The greatest amount of khat use was among respondents with PTSD who indicated that they found drugs help them to forget war experiences. The proposed mediated moderation model was supported by the data, i.e. besides the direct effects of PTSD and functional drug use on paranoia, the amount of khat use appeared to be a mechanism, by which paranoia is caused. We conclude that in our data we have uncovered a relationship between khat, PTSD and paranoia. Khat is functionally used by respondents with PTSD. Findings support a dose effect: the more khat consumption and when a respondent has PTSD, the higher the odds for paranoid ideation. However, the proposed causal chain needs to be confirmed in longitudinal studies. Demobilization and reintegration programs in Somalia need to be prepared to deal with complex psychological problems. (C) 2009 Elsevier Ltd. All rights reserved.